2020
DOI: 10.3390/cancers12020366
|View full text |Cite
|
Sign up to set email alerts
|

The IGF-II–Insulin Receptor Isoform-A Autocrine Signal in Cancer: Actionable Perspectives

Abstract: Insulin receptor overexpression is a common event in human cancer. Its overexpression is associated with a relative increase in the expression of its isoform A (IRA), a shorter variant lacking 11 aa in the extracellular domain, conferring high affinity for the binding of IGF-II along with added intracellular signaling specificity for this ligand. Since IGF-II is secreted by the vast majority of malignant solid cancers, where it establishes autocrine stimuli, the co-expression of IGF-II and IRA in cancer provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 176 publications
(156 reference statements)
1
24
0
Order By: Relevance
“…INS is one of the key growth factors for many types of neoplastic cells [32][33][34][35][36][37][38][39][40], and it is a potent growth factor for myeloma cells [20]. Our data fully confirm these dates and show that INS enhances serum-induced proliferation of RPMI8226 and IM9 cells (Figure 2A and Figure 2B).…”
Section: Effects Of Ins On the Cas-3 And Bcl-2 Mrna Expression Levelssupporting
confidence: 82%
“…INS is one of the key growth factors for many types of neoplastic cells [32][33][34][35][36][37][38][39][40], and it is a potent growth factor for myeloma cells [20]. Our data fully confirm these dates and show that INS enhances serum-induced proliferation of RPMI8226 and IM9 cells (Figure 2A and Figure 2B).…”
Section: Effects Of Ins On the Cas-3 And Bcl-2 Mrna Expression Levelssupporting
confidence: 82%
“…Later, it was demonstrated that both IGF ligands could initiate a mitogenic response via hybrid receptors such as IGF1R/IR or IGF1R/EGFR. Even in the absence of IGF1R, activation of the RAS‐MAPK–ERK signalling cascades can still be triggered by IGF2 through a specific isoform of the insulin receptor (IR A ) [14,24]. Therefore, any therapeutic strategy solely targeting IGF1R or IGF1R/EGFR and/or IGF1R/IR (main isoform) is likely insufficient to prevent the activation of downstream signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Escape mechanisms involving the heterodimerisation of IGF1R with either the human epidermal growth factor receptor (EGFR) or the insulin receptor (IR) have been described as underlying causes [11,12]. Alternative strategies are currently under investigation to prevent IGF1R activation, such as targeting its ligands (IGF1 and IGF2) with neutralising antibodies or combining anti‐IGF1R treatment with additional inhibitors of the PI3K/AKT and/or the RAS/MAP kinase cascades to avoid adaptive responses [13,14]. It seems crucial to identify biomarkers that can help to discriminate potential responders from non‐responders to IGF1R inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…In epidemiological studies, there is no clear association between IGF2 serum levels and cancer risk [43,44]. However, IGF2 is commonly upregulated in cancer and secreted by a broad range of tumor cell types [45][46][47][48]. Notably, IGF2 systemic effects modulate the syndrome known as non-islet cell tumor hypoglycemia [47,48].…”
Section: The Igf System In Cancer: a Complex Network Of Interactionsmentioning
confidence: 99%